Combining a Career in Clinical Practice and Research: The Benefits at Junior Career Level - Hiley, Jenny; Jerwood, Jed; Price, Jonathan; Thomas, Sian; Kenkre, Joyce (International Journal of Practice-based Learning in Health and Social Care, 2019)
Clinical academic careers programmes have developed in England and Wales to enable clinical staff outside of medical and dentistry – namely Nurses, Midwives, Allied Health Professionals, Pharmacists and Healthcare Scientists (NMAHPPS) to develop their academic and research skills alongside clinical practice. These schemes have complemented pre-existing national clinical academic careers pathways for Nurses, Midwives and Allied Health Professions (NMAHPs). Multi-professional case studies from the West Midlands and Wales are used to illustrate the benefits of clinical academic careers for individuals at junior career (pre-doctoral) level. The following case studies will be included: Jed Jerwood, an art psychotherapist, who is aspiring to be an evidence-based practitioner; Jonathan Price, a physiotherapist, who is developing support networks and navigating the system; and Sian Thomas, a nurse, who is developing opportunities to influence local and national practice. The benefits of clinical academic careers and the support from the English and Welsh programmes can be demonstrated in individuals at junior career level. A range of benefits are described including the emergence of autonomous evidence-based practitioners, developing their networks and collaborations, along with a plan for the future.